Lifestyle patterns in early pregnancy linked to gestational diabetes mellitus diagnoses when using IADPSG criteria. The St Carlos gestational study. Issue 3 (June 2016) - Ruiz-Gracia, Teresa; Duran, Alejandra; Fuentes, Manuel; Rubio, Miguel A.; Runkle, Isabelle; Carrera, Evelyn F.; Torrejón, María J.; Bordiú, Elena; Valle, Laura del; García de la Torre, Nuria; Bedia, Ana R.; Montañez, Carmen; et al.
Summary: Early-pregnancy lifestyle (EPL) could influence the development of gestational diabetes mellitus(GDM), depending on the diagnostic criteria used. Objective: We studied EPL in 1750 pregnant women using Carpenter-Coustan criteria(CCc), and in 1526 with the International Association of Diabetes and Pregnancy Study Groups criteria(IADPSGc). Methods: GDM risk factors were assessed in women between 24 and 28 weeks of gestational age during two consecutive years. A semiquantitative frequent-food-consumption questionnaire was used to evaluate lifestyle during pregnancy. Multiple logistic regression analysis was conducted to assess GDM risk with different lifestyle patterns. Results: Using IADPSGc, the GDM ORs (95%CI) for intake/week were: nuts >3 times: 0.59 (0.39–0.91; p < 0.015), refined cereals ≤1 serving: 0.72(0.58–0.89; p < 0.003), juices <4 servings: 0.77 (0.62–0.95; p < 0.017), cookies and pastries <4 servings: 0.71(0.57–0.89; p < 0.003) as compared to opposite habits. No significant nutritional patterns were found to be significant using CCc. The OR (95%CI) for GDM with none of the four risk patterns as compared to having three-four risk factors was 0.21(0.07–0.62; p < 0.005), remaining significant after stratification by BMI, age, obstetric events, parity and family history. The multiple logistic regression model including nutritional categories and pregestational BMI, age, obstetric history, parity, personal/family history, had an area under the curve(AUC) of the receiver operating curve(ROC) for the probability to predict GDM of 0.66 (CI 95%: 0.63–0.69; p < 0.001). Conclusion: Our study is the first to identify four early-pregnancy nutritional patterns associated with the GDM when using IADPSGc. Adherence to a low-risk nutritional pattern from early pregnancy on could be an effective strategy for GDM prevention.